2009
DOI: 10.1111/j.1540-8159.2009.02441.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardioversion for Atrial Fibrillation: Treatment Options and Advances

Abstract: Atrial fibrillation (AF) is associated with significant morbidity and mortality. There are two basic approaches to managing AF: slowing the ventricular rate, while allowing the arrhythmia to continue (the rate-control approach), and restoring and maintaining sinus rhythm (the rhythm-control approach) with antiarrhythmic drugs (AADs) and/or ablation, electrical cardioversion (CV), if needed, or both. Strategy trials comparing rate and rhythm control have found no survival advantage of one approach over the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 89 publications
(167 reference statements)
0
10
1
1
Order By: Relevance
“…Identifying which aspects of management influence successful cardioversion could lead to widespread uptake of those practices and abandonment of those that do not. Known patient factors associated with successful cardioversion include patient factors such as weight, 6 duration of arrhythmia, 7 and a history of hypertension. 6 Treatment factors include those affecting skin impedance, electrode placement, biphasic versus monophasic waveform, and initial and total energy.…”
Section: Importancementioning
confidence: 99%
“…Identifying which aspects of management influence successful cardioversion could lead to widespread uptake of those practices and abandonment of those that do not. Known patient factors associated with successful cardioversion include patient factors such as weight, 6 duration of arrhythmia, 7 and a history of hypertension. 6 Treatment factors include those affecting skin impedance, electrode placement, biphasic versus monophasic waveform, and initial and total energy.…”
Section: Importancementioning
confidence: 99%
“…6) Current therapies include antiarrhythmic drugs, electrical devices (pacemakers, defibrillators), and radiofrequency catheter ablation, all of which remain unsatisfactory for long-term management. 7) Of the more "unconventional" strategies for AF control, the pharmacological atrial defibrillator might prove to be particularly useful. Lurie, et al reported that significantly higher femoral vein and coronary sinus procainamide levels can be achieved by RA compared to peripheral venous drug infusion, 2) and the development of a device that delivers antiarrhythmic drugs into the right atrium or the superior vena cava has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Zabieg wykonuje się w krótkotrwałym znieczuleniu ogólnym. W obowiązujących wytycznych nie sprecyzowano, jakiej energii impulsu należy użyć, ale podkreśla się większą skuteczność prądu dwufazowego z początkową energią impulsu 150-200 J, z ewentualnym stopniowym zwiększaniem energii w kolejnych próbach [23]. Dowiedziono, że generatory dwufazowe są skuteczniejsze i wywołują mniejsze uszkodzenie miokardium [24].…”
Section: Kardiowersja Farmakologiczna I Elektrycznaunclassified